Job Satisfaction among Jordanian Psychiatric Nurses - Baker, Rasha Abu; Aisha Alshdefat, Aisha Alshdefat (International Journal of Psychosocial Rehabilitation, 2020)
Job satisfaction ranks highly as one of the main factors influencing turnover rates among psychiatric nurses. Psychiatric nursing has been reported to be a particularly stressful specialty, yet little is known about the level of job satisfaction among psychiatric nurses in Jordan. Psychiatric nurses have to cope with difficult patients, including some with multiple mental and substance use disorders who might be more aggressive or violent and present suicidal behaviors. Psychiatric nursing is also less valued and more stigmatizing than work in other health fields. Several studies have found that psychiatric nurses were particularly exposed to burnout, drug/alcohol abuse, and suicide. Similarly, Psychiatric nursing is considered more stressful than other specialties, which may explain the shortage of Psychiatric nurses, due to their difficult work conditions, mental health professionals are thus particularly affected by any change in the mental healthcare system.The purpose of this paper is to identify the relationship between job satisfaction and work in psychiatric unit among Jordanian psychiatric nurses.